Public accountability and open government in United Kingdom - Reid, Sir William (1995)
"Tracing briefly the logic of Ombudsman and availability of different institutions overseeing accountability in UK, the author (who is presently Ombudsman) discusses the role, jurisdiction and power of Ombudsman in UK and shares his experience on improving accountability of civil service. He then takes up for discussion various measures prevailing in UK to ensure openness in government"
Keywords: Public administration - Great Britain; Ombudsman - Great Britain; Ombudsman